The Intertextuality between Judg 5:12; Ps 68:19 (and its Syriac and Aramean Versions) and Eph 4:8. An approach from Sociological Stylistics - Pérez-Gondar, Diego (’Ilu. Revista de Ciencias de las Religiones, 2019)
Some intuitions of Sociological Stylistics are effective to better perceive how the intertextual dependence between documents is the reflection of a concrete and historical social dialogism. This approach helps to balance the historicist vision and does justice to the texts. This work analyzes the dependencies between Judg 5:12; Ps 68:19 and Eph 4:8, taking into account their different versions and points of view. These concrete texts show an intertextual dependence in which literality takes a secondary value with respect to the historical novelty that originates the new enunciation. In addition, each new context governs the use of the previous word endowed with authority and does so in order to preserve it. The Christian paschal mystery or the reconfiguration of Judaism after the destruction of the Temple (70 AD) conditions the way of updating an ancient text using it with new purposes.